“Bumi Becaro” Environmentally Community Empowerment Program to Supporting Post-Pandemic Economic Recovery for the Community of Payakabung Village, Ogan Ilir District - Saddam Husein; Purwanto, Wahyu; Anindita Paramasatya (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
This article explains how the condition of the community in the Payakabung Village area, North Indralaya District, Ogan Ilir Regency after the Covid 19 pandemic has not fully recovered, then there is the role of the surrounding company, namely PT PLN Indonesia Power UPDK Keramasan ULPL Indralaya in helping restore the socio-economic conditions of the community through the "Bumi Becaro" program. stands for " Bumi Lestari Caram Seguguk Bersamo " which means protecting the earth together. It is with this spirit that the community empowerment program in Payakabung Village is carried out using the Triple Bottom Line approach which focuses on the goals of the planet, people and profit, so that the programs implemented will have an impact not only on social and economic life but also pay attention to the environment so that the empowerment program will be sustainable. As a result, beneficiary groups feel the positive impact, socially this program produces new groups that are active in empowerment, economically there is an increase in people's income and environmentally this program also has a direct impact because it has a zero waste concept that supports the circular economy that is environmentally friendly.